Chapter The Historiae Florentini populi by Poggio Bracciolini. Genesis and Fortune of an Alternative History of Florence - Merisalo, Outi (Atti, 2020)
During the last years of his life, Poggio Bracciolini (1380-1459), former Apostolic Secretary and Chancellor of Florence, was working on a long text that he characterized, in a letter written in 1458, as lacking a well-defined structure. This was most probably his history of the people of Florence (Historiae Florentini populi, the title given in Jacopo's dedication copy to Frederick of Montefeltro, Duke of Urbino), revised and published posthumously by Poggio's son, Jacopo Bracciolini (1442-1478). Contrary to what is often assumed, Poggio's treatise was not a continuation, nor even a complement, to Leonardo Bruni's (1370-1444) official history of Florence. It concentrates on the most recent history of Florence from the fourteenth-century conflicts between Florence and Milan through Florentine expansion in Tuscany and finally reaching the mid-fifteenth century. This article will study the genesis and fortune of the work in the context of Poggio's literary output and the manuscript evidence from the mid-fifteenth century until the first printed edition of the Latin-language text by G.B. Recanati in 1715.